Effective Potential for binary mistures of a Bose-Einsten (e-Boletim da Física, 2019)
It has a degree, a master’s degree and a doctorate from the University of the State of Rio de Janeiro (UERJ). He has postdated at the Brazilian Center for Physical Research (CBPF). Hasexperience in the field of condensed matter physics, phase transition to finite temperature such ascondensation of Bose-Eistein. He developed a study on BCS-BEC crossover (CBPF). His research isnow centered on the study of gauge theories for gravitation, effective gauge theories with violationof Lorentz symmetry, and effects of spin-orbit interaction on a more fundamental physics via theweakly relativistic boundary of the Dirac equation.